The Effect of Employment Aspects on Poverty in Central Java Indonesia - Nur Imam Saifuloh; Abdul Aziz Ahmad; Suharno Suharno (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2019)
One way to tackle the problem of poverty is by understanding the labor aspects. This study aims to analyze the effect of employment aspects such as labor force participation rate, open employment rate and regional minimum wage on the poverty rate. This study used annual time series data between 2013-2017 of 15 regencies included in the red zone of poverty in Central Java Province. The best model to analyze data in this study is random effect model. The results show that labor force participation rate and open employment rate have positive and significant effect on poverty, while regional minimum wage has negative and significanteffect on poverty. The findings imply that the workforce should be well prepared to work or to create their own jobs andminimum wage should be increased.Keywords: Poverty, Employment, Random Effect Model.